2019
DOI: 10.20960/nh.2463
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease. Protein energy wasting. Nutritional assessment. Phase angle. Mid arm circumference.

Abstract: Background: Choosing the method of nutritional assessment is essential for proper follow-up of the nutritional status of patients undergoing liver transplantation. Objectives: Evaluate and compare the nutritional status of cirrhotic patients before and after liver transplantation over a year by different methods of nutritional assessment. Methods: Patients undergoing liver transplantation were assessed in five phases: pre-transplant, 1, 3, 6 and 12 months after transplantation at the hospital Santa Casa de Mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In 89 ICU patients, a PhA less than less than 5.5° showed an accuracy of 79% in identifying patients at high nutrition risk (NUTRIC score ≥5) [ 19 ▪ ]. In renal replacement therapy patients, a PhA cut-off of 4.6° has been shown to predict malnutrition, defined by protein--energy wasting [ 36 , 37 ]. A study comparing the accuracy of BIVA, versus the definition according to ESPEN in hospitalized patients, in predicting malnutrition, found that BIVA might be the superior method [ 38 ].…”
Section: Nutrition Managementmentioning
confidence: 99%
“…In 89 ICU patients, a PhA less than less than 5.5° showed an accuracy of 79% in identifying patients at high nutrition risk (NUTRIC score ≥5) [ 19 ▪ ]. In renal replacement therapy patients, a PhA cut-off of 4.6° has been shown to predict malnutrition, defined by protein--energy wasting [ 36 , 37 ]. A study comparing the accuracy of BIVA, versus the definition according to ESPEN in hospitalized patients, in predicting malnutrition, found that BIVA might be the superior method [ 38 ].…”
Section: Nutrition Managementmentioning
confidence: 99%
“…The PhA has been used as an predictor of health status in different clinical situations, 6 such as undernutrition, 7,8 liver diseases, 9 chronic kidney disease, 10,11 and critical illness 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…3 Because of the geometric relationship between resistance and reactance, which includes body cell mass and fluids, PhA still reflects cell function and integrity even in hyperhydration status. 2 The PhA has been used as an predictor of health status in different clinical situations, 6 such as undernutrition, 7,8 liver diseases, 9 chronic kidney disease, 10,11 and critical illness. 12,13 The PhA at 50 kHz frequency has been shown to be a predictive parameter for prognosis and mortality in critically ill adults.…”
Section: Introductionmentioning
confidence: 99%